Ichthyofaunal assemblage in the mangrove community of University Town, Catarman, Northern Samar - Chan, Kiara Adenelle A. (2022)
Mangroves are widely known as feeding and nursery grounds for various marine organisms. These ecosystems are an ideal transitional habitat for reef fishes before reaching adulthood. Mangrove ichthyofaunal assemblages in Northern Samar have remained poorly studied. Specifically, the study aimed to document and describe fish species present in the mangrove community of University Town, Catarman, Northern Samar; determine the fish diversity and richness; and correlate the presence and abundance of fishes in the mangroves with substrate type, pH, and water temperature. The fishes were sampled using trap and mosquito nets in three sampling sites inside the mangrove community. The collected samples were sorted, measured, weighted, and identified in and outside the field. The fish catch was composed of 149 individuals belonging to 13 species. The most abundant species were Atherinomorus endrachtensis (36.242%), followed by followed by Fibramia amboinensis (18.792%), erapon jarbua (14.094%), Sphaeramia orbicularis (10.67%). The dominant families were the silversides (Atherinidae) and cardinalfishes (Apogonidae). Most of the reported species were less than 10 cm (98.658%), juveniles (55.705%), and reef-associated (81.208%), suggesting the nursery role of the mangrove community. Of the three sampling sites, the sandy-rocky Site 1 had the highest abundance, while species diversity and richness were the highest in the muddy-rocky Site 1 had the highest abundance, while species diversity and richness were the highest in the muddy-rocky Site 2. Fish abundance showed a weak negative correlation with temperature (r= -0.16) and a very weak positive correlation with pH (r=0.02). Overall, the ichthyofaunal assemblage in University Town mangroves exhibited "poor diversity", "semi-balanced", and "semi-disturbed" status.